Economic Analysis of Alternative Ware Potato Storage Technologies in Uganda - Wauters, P.; Naziri, D.; Turinawe, A.; Akello, R.; Parker, M. (Springer, 2022)
In Uganda, potato is primarily grown as a cash crop and smallholder farmers sell majority of their produce immediately after harvest. Only a few farmers store ware potato for later sale using various traditional storage methods. Main reasons are farmers’ immediate need for cash, the low volumes of potato harvested, fear of loss during storage due to pests and diseases, and a lack of adequate storage facilities. In order to exploit the seasonal market price fluctuations and increase the economic return of potato farming, improved individual and collective ambient ware potato storage units were introduced. Unlike traditional storage facilities that maintain the marketability of stored potato up to five weeks only, improved ambient stores can maintain their marketability up to nine weeks. This article uses cost-benefit analysis methods to compare the economic performance of improved ambient stores with traditional storage facilities. Results indicate that few of the traditional and improved collective storage units generated profit, an aspect that was attributed to management challenges. The improved individual stores performed overall well, generating higher profit margins than improved collective stores. Improved individual stores had an average payback period of three to four years that could even be reduced to less than one year if used at full capacity. Due to their characteristics, improved individual ambient ware potato stores thus seem to be particularly suitable to substantially increase the income of potato farming households.